2010
DOI: 10.1262/jrd.09-090e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unilateral Electrolytic Lesion of the Dorsomedial Nucleus of the Hypothalamus on Milk-ejection Reflex in the Rat

Abstract: Abstract. The dorsomedial nucleus of the hypothalamus (DMH) has been suggested to be a final relay site for the afferent pathway of milk-ejection reflex (MER). The present experiments were undertaken to examine whether unilateral lesion of the DMH abolished MER induced by unilateral suckling by pups. The unilateral DMHs of urethaneanesthetized lactating rats were electrolytically lesioned. Then 5 pups were applied to nipples ipsilateral or contralateral to the lesioned DMH and the intramammary pressure was mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In addition to our previous results indicating that some DMH cells projected to the SON in both sides of the hypothalamus [11,12,13], the results of the present experiment suggesting the existence of excitatory connections between OT cells in the bilateral hypothalamus would be a good base supporting a synchronization of burst discharges of OT cells in separate magnocellular nuclei.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In addition to our previous results indicating that some DMH cells projected to the SON in both sides of the hypothalamus [11,12,13], the results of the present experiment suggesting the existence of excitatory connections between OT cells in the bilateral hypothalamus would be a good base supporting a synchronization of burst discharges of OT cells in separate magnocellular nuclei.…”
Section: Discussionsupporting
confidence: 81%
“…Our previous studies on the DMH showed that the cells in the DMH on one side projected to the SON in both sides of the hypothalamus. However, there were not many cells in the DMH projecting to the SON in both sides of the hypothalamus [11,12,13]. So it seems unlikely that such a small number of DMH cells fully support synchronization of 9000 OT cells in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrical stimulation of the DMH facilitates OT neuronal activity in the SON. 154 However, the importance of the DMH per se is still clouded by the possibility that fibers of passage are responsible for both orthodromic and antidromic responses to SON stimulation, as well as lesion effects. 152 Unilateral electrolytic lesions of the DMH completely block suckling to contralateral (but not ipsilateral) suckling.…”
Section: Hypothalamic Circuitrymentioning
confidence: 99%